Reconsidering the Bound Captive Statuettes from the Pyramid Complex of Raneferef - Prakash, Tara.
Previous scholars have hypothesized that a group of nine wooden statuettes of bound foreign captives from the funerary temple of Raneferef had originally been part of an article of furniture, most likely a royal throne. This article reassesses these arguments. Visual analysis suggests that four different artists, who were working within two distinct groups or “workshops,” carved the statuettes. As a result, it seems most likely that the statuettes were actually part of two different objects. Moreover, comparison with preserved chairs and thrones, as well as ancient images of them, demonstrates that the Raneferef captives do not readily fit this context. Rather, most likely the statuettes had been part of two statue naoi or shrines.   doi: http://dx.doi.org/10.5913/jarce.54.2018.a012